Learning experience of machining carbon fibre CFRP AL2024 using Design of Experiment (DoE) approach - Saiful Bahri, Mohamed; Alias, Mohd; Jailani, Ismail (2020)
The rapid technological changes required that Technical & Vocational Education Training, TVET’s trainees continuously update their knowledge and skills especially in the machining sectors. Traditionally, trainees are only trained to be a good machinist through theory and practical sessions however; they do not equipped with the mastery of underlying knowledge and scientific principles. Present teaching approach of machining cannot provide solid solution on these issues. This paper describes the implementation of Design of Experiment (DoE) methodology on machining composite materials via design expert software. The main objective of this paper is to share learning experience of machining CFRP Al2024 and propose the generic approach of implementing DoE in machining as an embedded technique for trainees to re-skilling and continuing professional development. It was revealed that the generic approach established the relation between the cutting parameters and the response variable to perform analysis and optimization correctly.